(untitled) (Bangladesh Journal of Animal Science, 2018)
This study was conducted to evaluate the effect of garlic an alternative feed additive in broiler diet. The experiment was carried out for a period of 32 days with a number of 340 day-old straight run broiler chicks. Birds were divided into five dietary treatment groups with 4 replications each having 17 birds. The dietary groups were; control (basal diet; no additives), antibiotic (basal diet + antibiotic), garlic 0.25% (basal diet + 0.25% garlic powder), garlic 0.50% (basal diet + 0.50% garlic powder) and garlic 0.75% (basal diet + 0.75% garlic powder). Results showed that the body weight, body weight gain and total FCR were not differ significantly (P>0.05) among the treatment groups. Total feed intake in different dietary levels showed significant (P<0.05) difference. Control group showed significantly (P<0.05) higher feed intake than the other dietary groups. The results also showed thatthe serum glucose concentration was reduced (P<0.05) in all garlic supplemented groups compared to the control and antibiotic groups. Total cholesterol level was significantly (P<0.05) lower in the 0.75% garlic group compared to the control and antibiotic groups. In case of dressing parameter, 0.75% garlic group showed lowest (P<0.05) abdominal fat compared to the other groups. Cost of production per kg live broiler was lower in antibiotic and control groups compared to the garlic group. With regards to profit, antibiotic groups showed higher profitability than the other groups. It can be concluded that the addition of garlic powder to broiler diet had positive effect on cholesterol and glucose levels and had no effect on feed intake, body weight gain, meat yield, bone development, carcass parameters. It can be suggested that the garlic could be a potential feed additive in broiler diet. Bang. J. Anim. Sci. 2017. 46 (4): 215-224